2007
DOI: 10.1159/000100786
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of a Large Subchorionic Placental Cyst with Intracystic Hematomas

Abstract: A large intrauterine cyst containing a heterogenous mass was found by ultrasound in the placenta of a 35-year-old gravida 2 para 1 woman. The cyst, measuring 10.9 × 10.1 cm with a heterogenous mass shadow, was attached near the placental cord insertion site. The woman delivered a healthy female baby weighing 3,330 g by cesarean section without complication. A histopathological examination revealed that the lesion was a subchorionic cyst and contained an internal hematoma. Large subchorionic cysts are extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…There have been few reports regarding placental surface cysts with intracystic hemorrhaging. Including the present case, we conducted a review of literature pertaining to placental surface cysts (Table ) . Of the 42 cases of placental surface cysts, four cases (10%) developed intracystic hemorrhaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been few reports regarding placental surface cysts with intracystic hemorrhaging. Including the present case, we conducted a review of literature pertaining to placental surface cysts (Table ) . Of the 42 cases of placental surface cysts, four cases (10%) developed intracystic hemorrhaging.…”
Section: Discussionmentioning
confidence: 99%
“…Including the present case, we conducted a review of literature pertaining to placental surface cysts ( Table 1). [1][2][3][4][5][6][7] Of the 42 cases of placental surface cysts, four cases (10%) developed intracystic hemorrhaging. Our review findings suggested that, of the 38 cases without intracystic hemorrhaging, five cases (13%) developed FGR, and preterm delivery occurred in 14 cases (37%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Пролонгированное течение МСХТ дает возможность диагностировать данное критическое состояние, провести необходимую терапию для коррекции дисфункции фетоплацентарного комплекса, принять решение о возможности пролонгирования беременности [6]. При массивном субхориальном тромбозе сгусток отделяет хориальную пластинку от ворсинчатого хориона и возникают гипотрофия, дистресс и перинатальная гибель плода [6][7][8].…”
Section: рис 2 петли пуповины в структуре образования (обозначены сunclassified